Nanoparticles: An Experimental Study of Zinc Nanoparticles Toxicity on Marine Crustaceans. General Overview on the Health Implications in Humans - Vimercati, Luigi; Cavone, Domenica; Caputi, Antonio; De Maria, Luigi; Tria, Michele; Prato, Ermelinda; Ferri, Giovanni Maria (Frontiers in Public Health, 2020)
Abstract: The presence of products containing nanoparticles or nanofibers is rapidly growing. Nanotechnology involves a wide spectrum of industrial fields. There is a lack of information regarding the toxicity of these nanoparticles in aqueous media. The potential acute toxicity of ZnO NPs using two marine crustacean species: the copepod Tigriopus fulvus and the amphypod Corophium insidiosum was evaluated. Acute tests were conducted on adults of T. Fulvus nauplii and C. insidiosum. Both test species were exposed for 96 hours to 5 increasing concentrations of ZnO NPs and ZnSO4H2O, and the endpoint was mortality. Statistical analysis revealed that the mean LC50 values of both ZnO NPs and ZnSO4H2O (ZnO NPs: F=59.42; P<0.0015; ZnSO4H2O: F=25.57; P <0.0015) were significantly lower for Tigriopus fulvus than for Corophium insidiosum. This result confirms that the toxic effect could be mainly attributed to the Zn ions, confirming that the dissolution processes play a crucial role in the toxicity of the ZnO NPs.